Pelatihan Penyusunan Modul Penyelenggaraan P5 Berbasis Potensi Kearifan Lokal: Training for Preparing P5 Implementation Module based on Local Wisdom Potential - Mawarti, Rista Ayu; Rizki, Andien Amelia; Isnaini, Errima Adqha (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This article aims to analyze the process and impact of the Local Wisdom-Based Module Development Training for the Pancasila Student Profile Strengthening Project (P5) at SMAN 1 Turen. The method used is community empowerment, involving teachers as the primary subjects. The training includes identifying local potential, guiding module development, and implementing and evaluating the modules. The first result shows an increase in teachers' understanding of the importance of local wisdom in developing relevant P5 modules. The second result indicates that the training positively impacts teachers' competence in integrating local wisdom into learning, enhancing the relevance and sustainability of P5. Additionally, there is an increase in student participation in P5 activities following the implementation of local wisdom-based modules. The training proves effective in improving P5 implementation quality at SMAN 1 Turen and can serve as a model for other schools.